Some reflections between city form and mobility.: Dilemma between past and present. - Balletto, Ginevra (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Urban development is closely linked by a continuous cause - effect alternation of technology that finds its maximum application in the city, and in particular in the transport system to support the multiple forms of mobility. From the historical reading of urban processes, it is in fact possible to extrapolate strengths and weaknesses, positive and negative externalities, of mobility and recognize the recurring elements in the evolution of the city form. The aim of the paper is to build a reorganization of knowledge between literature and comparisons of city forms to extrapolate from the past possible approaches to evaluate the present on the occasion of multiple and contextual transitions such as energy, digital and ecological ones.